The Impact of Government Dual Policy on the Selection of OEM's Regulatory Strategy for Third-Party Remanufacturing. (12th July 2022) - Cheng, Hongya; Meng, Lijun; Huang, Zuqing
Abstract : Remanufacturing plays an important role in the circular economy and environmental protection. In the development of the remanufacturing closed-loop supply chain (CLSC), the impact of government policy cannot be ignored. However, previous studies have rarely answered the impact of government dual policy (the policy combination of trade-old-for-remanufactured and carbon tax policy) on the optimal decisions of CLSC enterprises. To fill the gap, this work considers the remanufacturing modes and government dual policy simultaneously and investigates a CLSC of waste of electronic and electrical equipment (WEEE) consisting of an original equipment manufacturer (OEM) and a third-party remanufacturer (TPR). Here the OEM has three strategies for regulating third-party remanufacturing activities: outsourcing (Model O), authorization (Model A), and nonregulation (Model D). The results show that: (i) Whether the government implements the dual policy or not, Model O is the best choice for OEM. And compared with nongovernment policy intervention, government dual policy can improve the recovery rate of WEEE products and then effectively promote the recycling of waste resources; (ii) When the government dual policy parameters meet a certain condition, the dual policy could effectively increase supply chain members' profits and the total profits of CLSC and boost market demand expansion; (iii) Compared with the other two remanufacturing modes, the CLSC under nonregulation strategy is the optimal remanufacturing mode for the whole society; meanwhile, OEM nonregulation strategy is the worst strategy for the environmental protection. In addition, when the government sets appropriate parameters, government dual policy is beneficial to the consumer, supply chain member, and the society simultaneously, but the impact of the dual policy on the environment is also related to the ratio of the two products' impact on the environment.